Post-transplant malignancies in pediatric liver transplant recipients: Experience of two centers in Turkey - Karakoyun, Miray; Önen, Şebnem; Baran, Maşallah; Çakır, Murat; Ömür Ecevit, Çiğdem; Kılıç, Murat; Kantar, Mehmet; Aksoylar, Serap; Özgenç, Funda; Aydoğdu, Sema (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: A liver transplant is the preferred treatment for patients with end-stage liver disease, as it usually results in long-term survival. However, due to the use of chronic immunosuppressive therapy, which is necessary to prevent rejection, de novo cancer is a major risk after transplantation. The aim of this study was to assess the incidence of post-transplant malignancies in children after liver transplantations. Materials and Methods: The study group consisted of 206 liver transplant recipients, with no history of cancer, including hepatocellular carcinoma, in two liver transplantation centers in Turkey between 1997 and 2015. Data were obtained from patient’s data chart. Results: In the study group, de novo cancer was diagnosed in 13 of the 206 patients. Post-transplant lymphoproliferative disease (PTLD) occurred in seven (53.8%) patients and other malignancies in six of the 13 patients. The types of PTLD were as follows: B-cell origin (n=2), Epstein-Barr virus (EBV)-related (n=2), T-cell origin (n=1), and Hodgkin’s lymphoma (n=2). EBV DNA was isolated from seven patients, three of whom developed PTLD. The others developed Kaposi’s sarcomas, Burkitt’s lymphomas, cutaneous large-cell lymphomas, Hodgkin’s lymphomas, and liver sarcomas. Conclusion: After transplantation, immunosuppressive treatment is unavoidable, increasing the risk of malignancies. However, a close follow-up and periodic screening can reduce cancer-related mortality and morbidity. Cite this article as: Karakoyun M, Önen Ş, Baran M, et al. Post-transplant malignancies in pediatric liver transplant recipients: Experience of two centers in Turkey. Turk J Gastroenterol 2018; 29: 85-9.